Mouse models of tooth abnormalities - Fleischmannova, Jana; Matalova, Eva; Tucker, Abigail S; Sharpe, Paul T (European journal of oral sciences, 2008)
Tooth number is abnormal in about 20% of the human population. The most common defect is agenesis of the third molars, followed by loss of the lateral incisors and loss of the second premolars. Tooth loss appears as both a feature of multi-organ syndromes and as a non-syndromic isolated character. Apart from tooth number, abnormalities are also observed in tooth size, shape, and structure. Many of the genes that underlie dental defects have been identified, and several mouse models have been created to allow functional studies to understand, in greater detail, the role of particular genes in tooth development. The ability to manipulate the mouse embryo using explant culture and genome targeting provides a wealth of information that ultimately may pave the way for better diagnostics, treatment or even cures for human dental disorders. This review aims to summarize recent knowledge obtained in mouse models, which can be used to gain a better understanding of the molecular basis of human dental abnormalities.
Keywords: Models, Animal; abnormality zubů; fenotyp; anodoncie; zuby přespočetné; Phenotype; Tooth, Supernumerary; Bone Morphogenetic Protein 4; Odontogenesis; kostní morfogenetický protein 4; kostní morfogenetické proteiny; Bone Morphogenetic Proteins; parodont; fosfoproteiny; zubní sklovina; dentin; Phosphoproteins; Periodontium; trans-aktivátory; Dental Enamel; Animals; lidé; Transcription Factors; transkripční faktory; Humans; Tooth Abnormalities; odontogeneze; zvířata; myši; modely u zvířat; Trans-Activators; Mice; Dentin; Anodontia